1997
DOI: 10.1002/(sici)1097-0231(199707)11:11<1194::aid-rcm935>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polydisperse synthetic polymers by size-exclusion chromatography/matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Synthetic polymers having a polydispersity greater than 1.1 cannot be reliably characterized by matrix-assisted laser desorption/ionization (MALDI) time-of-flight mass spectrometry alone. This complication has been overcome by off-line coupling of size-exclusion chromatography (SEC) with MALDI. Data are presented for a wide variety of synthetic polymers having polydispersities from 1.7 up to 3.0. Polystyrene (15 kDa and 48 kDa), polybutylacrylate (62 kDa), polycarbonate (28 kDa), aromatic polyester resin (8 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 16 publications
(21 reference statements)
4
79
0
Order By: Relevance
“…Offline GPC coupling has been accomplished by fraction collection, primarily for high molecular weight polymers. [51] Monomers' structure and end groups were determined using the delayed extraction reflectron mode. Offline fraction collection is both laborious and time consuming but MS settings can be optimized for each individual fraction.…”
Section: Qualitative Characterization Of Lmw Compoundsmentioning
confidence: 99%
“…Offline GPC coupling has been accomplished by fraction collection, primarily for high molecular weight polymers. [51] Monomers' structure and end groups were determined using the delayed extraction reflectron mode. Offline fraction collection is both laborious and time consuming but MS settings can be optimized for each individual fraction.…”
Section: Qualitative Characterization Of Lmw Compoundsmentioning
confidence: 99%
“…(8) is 1, the constant a can be calculated by (9) Solving Eqs. (6) and (9) for kf gives (10) Using k′f obtained from Eq. (5) and observed If,i, one can calculate the response factor kf for each f-th fraction.…”
Section: Theorymentioning
confidence: 99%
“…The average molecular weight of the original polymer samples can be calculated by using SEC chromatograms thus calibrated. Various applications using SEC/MALDI-MS have been reported for the characterization not only of homopolymers such as polystyrene (PS), 10 poly(methylmethacrylate) (PMMA), 11,12 polycarbonates, 10,13,14 and polyesters, 10,15 but also of some copolymers 10,11,[15][16][17] and polymer blends. 18 However, it should be noted that correct molecular weight distribution might not be necessarily obtained even by SEC/MALDI-MS, mainly due to the band broadening on the SEC chromatogram and inadequate calibration, as was theoretically pointed out by Lou et al 19 The former band broadening is frequently encountered in SEC measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, Garozzo et al [11] showed that agreement between molecular mass distributions of polysaccharides determined by MALDI-MS and SEC was improved if polydispersities were low. Similarly Montaudo et al [12] found that molecular mass distributions of polydimethylsiloxanes determined by MALDI and SEC agreed if polydispersities were low, while Nielen and Malucha [13] showed that synthetic polymers with a polydispersity greater than 1.1 could not be reliably characterized by MALDI-MS. The high mass components of blends of two polymers of narrow polydispersity suffered from mass discrimination [14], giving lower intensities than expected for the high mass ions.…”
Section: Introductionmentioning
confidence: 99%